Social vulnerability and health status: a household survey in the central area of a Brazilian metropolis Vulnerabilidade social e estado de saúde: inquérito domiciliar em uma metrópole brasileira - Rita Barradas Barata; Manoel Carlos Sampaio de Almeida Ribeiro; Ana Carolina Cassanti (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The self-rated health in a sample of adults living in the central area of São Paulo, Brazil, was studied by comparing a group of residents in census tracts without social vulnerability, identified using an indicator developed by the SEADE Foundation, and a group of residents in census tracts with middle, high or very high social vulnerability. Subject age and sex were used as control variables while family income, education level, degree of happiness, adequacy of income, satisfaction with the neighborhood and sense of discrimination were the intervening variables selected. After adjustment in the hierarchical model the self-rated health status was inversely associated with social vulnerability, age and sense of discrimination, and directly related to income, education level and degree of happiness. Satisfaction with the neighborhood and adequacy of income lose significance after adjustment. The degree of happiness is the variable with the greatest strength of association with health status even after controlling for other variables. O estado de saúde autorreferido de uma amostra de adultos residentes na área central do Município de São Paulo, Brasil, foi estudado comparando-se um grupo de residentes em setores censitários sem vulnerabilidade social, segundo o indicador elaborado pela Fundação SEADE, e um grupo de residentes em setores censitários com média, alta ou muito alta vulnerabilidade social. A idade e o sexo foram utilizados como variáveis de controle, enquanto a renda familiar, o grau de escolaridade, o grau de felicidade, a adequação do nível de renda, a satisfação com a vizinhança e a sensação de discriminação foram as variáveis intervenientes selecionadas. Após o ajuste no modelo hierárquico, o estado de saúde autorreferido mostrou associação inversa com a vulnerabilidade social, idade e sensação de discriminação e relação direta com a renda, a escolaridade, o grau de felicidade. A satisfação com a vizinhança e a adequação do nível de renda perdem significância após o ajuste. O grau de felicidade é a variável com maior força de associação com o estado de saúde mesmo após o controle pelas demais variáveis.